International relations since 1945 a global history - Young, John W. 1957-; Kent, John 1949- (Oxford University Press, 2004)
International Relations Since 1945: A Global History is an authoritative and historical analysis of international relations during the Cold War and its aftermath. In one volume, it both describes and interprets events since 1945 for an undergraduate audience. Exploring how the Cold War affected world politics as a whole, the book also deals with such important regional problems as the Middle East wars, the development of European integration, and the end of the European empires in Africa and Asia.